Synthesis of New Oxido-Vanadium Complexes: Catalytic Properties and Cytotoxicity. (January 2018) - Das, Uttam; Pattanayak, Poulami; Santra, Manas Kumar; Chattopadhyay, Surajit
Reaction of 2, 3-dihydroxy benzaldehyde with 2-(2-amino phenyldiazenyl)phenol afforded the ligand 3-(2-(2-hydroxyphenyl)diazenyl)-4-alkylphenyliminomethyl)benzene-1, 2-diol. Reaction of H2 L with VOSO4 . 5H2 O gave the oxido-vanadium(IV) complexes [(L)VO], which exhibited a quasi-reversible oxidative cyclic voltammetric response in a V(IV)/V(V) oxidative process. The complexes act as catalysts in the oxidation of organic thioethers and bromination of phenol. Their cytotoxic properties were examined for three cancer cell lines.